2011
DOI: 10.1352/1944-7558-116.1.48
|View full text |Cite
|
Sign up to set email alerts
|

Peer-Related Social Competence of Young Children With Down Syndrome

Abstract: The peer-related social competence of children with Down syndrome was examined in an observational study. Dyadic interactions with peers of children with Down syndrome were compared to the dyadic interactions of matched groups of typically developing children and with playmates differing in both familiarity and social skills. Results suggested that both risk and protective factors influenced the peer interactions of children with Down syndrome. Recommendations were made for applying contemporary models of peer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 61 publications
1
14
0
1
Order By: Relevance
“…Children with disabilities who have friends also present better results in behavioral characteristics such as activity level, reactivity, goal-directedness, and responsiveness to adults (Buysse, 1993). In an inclusive setting, friends without disabilities can be an important resource for children with disabilities to develop social competence (Guralnick, 1990) because they tend to support and scaffold dyadic interactions (Guralnick, Connor, & Johnson, 2011).…”
Section: Friendshipmentioning
confidence: 99%
“…Children with disabilities who have friends also present better results in behavioral characteristics such as activity level, reactivity, goal-directedness, and responsiveness to adults (Buysse, 1993). In an inclusive setting, friends without disabilities can be an important resource for children with disabilities to develop social competence (Guralnick, 1990) because they tend to support and scaffold dyadic interactions (Guralnick, Connor, & Johnson, 2011).…”
Section: Friendshipmentioning
confidence: 99%
“…Laboratory and interview studies report that although children with communication difficulties may have problems in displaying peer competence, their peers are still key facilitators of social inclusion (Bat-Chava & Deignan, 2001;Guralnick, Connor, & Johnson, 2011;Kamenopoulou, 2012;Nordstrom, 2011;Summers, 1997). Ethnographic studies and conversation analyses in disability research show that with complex needs.…”
mentioning
confidence: 99%
“…Some studies showed that that the families of children with DS found inclusion classes at preschool appropriate, however, they did not accept since the mainstreaming classes did not provide appropriate opportunities for their children Guralnick, Connor, & Johnson, 2011;Kasari, Freeman, Bauminger, & Alkin, 1999). When the findings of this research are examined, it is seen that there is a lack of a circular on how to apply the mainstreaming practices at the beginning of the school year.…”
Section: Discussionmentioning
confidence: 83%
“…Even if the term changes, games, and peer groups are expressed as the environments in which the social interaction of the special needs children develops the most. Social interaction between peers has been a subject of interest and work for many years due to its importance (Guralnick, Connor, & Johnson, 2011). The National Association for the Education of Young Children has also emphasized the importance of educating preschoolers about gaming activities to assess, support and monitor the development of all children and has shown it as among the indispensable values in the child's life (National Association for the Education of Young Children, NAEYC) (Division for Early Childhood National Association for the Education for Young Childen, DEC, 2009).…”
Section: Explore Importance Of the Problemmentioning
confidence: 99%